Self-extension in the digital world: conceptual framework proposal - Alves Garcia, Sheila Farias [UNESP]; Marchi, Gabriela de Melo [UNESP]; Jungles, Bruna Ferreira (Univ Nove Julho, 2020)
Objective: The present study aimed to understand how consumers express consumption experiences in the virtual environment and how these postings relate to self-extension. Method: The assessment was based on observations of self-presentation that emerged from the users' postings in the Vivino application (a community for wine lovers), complemented by qualitative interviews. Content analysis was utilized for the observations and hermeneutics, in the interviews. Originality/Relevance: To explore the symbolic aspects of wine consumption using a qualitative research approach based on non-participant observations of the application Vivino, a virtual collaborative community for wine lovers, to comprehend the extension of 'self reflected in the digital world. Results: Among the reasons that explain consumer participation in consumer communities is the fascination that sharing has over individuals, leading them to develop the need to participate in the spectacle, to give meaning to their existence, in a society mediated entirely by images. Theoretical/Methodological Contributions: In order to represent the main findings of this study, a conceptual framework of the process of formation of the extended self in the digital environment was developed, based on the evidence extracted from empirical observations.
Keywords: Identity; Digital Extended Self; Conceptual Framework; Wine Consumption; Vivino